Evidence Based Public Health Policy in Mexico: A Systematic Review (Revista de Medicina Clinica, 2025)
Introduction: Evidence-based public policy in Mexico seeks to ground government decisions in rigorous empirical evidence rather than relying solely on expert opinion or political pressures.  Methods: We performed a systematic search of PubMed, Scopus, and Google Scholar for publications from 2000 to 2024 using the keywords “evidence-based policy” and “policy-making.” Both conceptual analyses and empirical evaluations of international literature and Mexican health-system reforms were included. Identified studies were categorized thematically into historical evolution, Seguro Popular, INSABI, and current system performance. Results: Our review identified three successive generations of evidence-informed reforms in Mexico’s health sector. The first (1940s–1960s) involved consolidating the Mexican Social Security Institute (IMSS) and separating corporate functions. The second (1970s–1990s) emphasized primary care strengthening and decentralization, supported by newly generated epidemiological data. The third phase culminated in the creation of Seguro Popular in 2003, underpinned by formal evaluation mechanisms. Seguro Popular expanded coverage and reduced catastrophic out-of-pocket spending but faced sustainability challenges due to political resistance and budgetary constraints. The abrupt transition to INSABI in 2020 exposed planning and financing weaknesses, disrupted service provision, and increased household health expenditures. Persistent subnational disparities in access, efficiency, and avoidable mortality continue to reflect institutional fragmentation. Conclusions: While Mexico’s evidence-based reforms have clearly improved coverage and financial protection, achieving true equity requires strengthening data quality, building robust institutional capacity, enhancing adaptive governance mechanisms, and securing long-term financial sustainability. Addressing these foundational challenges will be essential to ensure that future policy decisions remain firmly rooted in the best available evidence.